2021
DOI: 10.1038/s41398-021-01361-3
|View full text |Cite
|
Sign up to set email alerts
|

Maternal immune activation generates anxiety in offspring: A translational meta-analysis

Abstract: Maternal immune activation (MIA) during pregnancy is recognized as an etiological risk factor for various psychiatric disorders, such as schizophrenia, major depressive disorder, and autism. Prenatal immune challenge may serve as a “disease primer” for alteration of the trajectory of fetal brain development that, in combination with other genetic and environmental factors, may ultimately result in the emergence of different psychiatric conditions. However, the association between MIA and an offspring’s chance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 53 publications
2
14
0
Order By: Relevance
“…Importantly, recent evidence shows that hRSV can infect placental cells, cross the placental barrier, and, therein, be vertically transmitted to the fetus [18,24,40]. One of the unknown relevant issues is the MIA effect on hRSV infection, which is essential since MIA has been associated with cognitive and behavioral impairment and neuropsychiatric illnesses such as SCZ and ASD [32,53,57,94]. The critical information about the harmful effect of MIA on the neurodevelopment of the fetus with neurological consequences in adulthood came from the Poly: IC model, which provides valuable evidence of the alteration of neurotransmitters pathways and cytokines expression that affect brain development [95,96].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, recent evidence shows that hRSV can infect placental cells, cross the placental barrier, and, therein, be vertically transmitted to the fetus [18,24,40]. One of the unknown relevant issues is the MIA effect on hRSV infection, which is essential since MIA has been associated with cognitive and behavioral impairment and neuropsychiatric illnesses such as SCZ and ASD [32,53,57,94]. The critical information about the harmful effect of MIA on the neurodevelopment of the fetus with neurological consequences in adulthood came from the Poly: IC model, which provides valuable evidence of the alteration of neurotransmitters pathways and cytokines expression that affect brain development [95,96].…”
Section: Discussionmentioning
confidence: 99%
“…During pregnancy, the viral infection promotes MIA, which has been associated with alterations in the neurodevelopment of the fetus, such as cognitive impairment and neuropsychiatric illness [48][49][50]. Several studies using pregnant animal model exposure to polyriboinosinic-polyribocytidylic acid (Poly: IC) show detrimental effects on the brain of the fetus development, promoting neurological outcomes in adulthood [32,48,[51][52][53]. It has been observed that the Poly: IC treatment in animals during pregnancy promote alterations in the neurotransmitters signaling such as dopamine (DA), γ-aminobutyric acid (GABA), and serotonin (5-HT) at different gestational stages [54][55][56][57].…”
Section: Hrsv Infection During Gestation: Possible Impairment Of Fetal Neurodevelopment?mentioning
confidence: 99%
“…Anxiety has also been linked to changes within the immune system, which is interesting in the current context, given that HAZ are less anxious than LAZ. For example, a recent study in mice showed that IL-17a secreted from meningeal γδ17 T cells expressing high levels of chemokine receptor 6 regulates anxiety-like behaviour [ 60 ] and a recent meta-analysis found that maternal immune activation during pregnancy induces anxiety behaviour in offspring [ 61 ]. In line with these findings, LAZ and HAZ show differences in cytokine expression ( il12bb , tnfrsf1b , cxcl12b , ccl35.2 and macrophage expressed 1, tandem duplicate 2 ) chemokine receptor expression ( xcr1a.1 , xcr1b.1 , ccr11.1 and ccr8.1 ) and other genes related to immune system activity ( ptgr1 , ltb4r2b , ltc4s , tlr4ba and toll-like receptor 8a ).…”
Section: Discussionmentioning
confidence: 99%
“…In the last few years, there has been a growing interest in neurodevelopmental disorders (NDDs) related to maternal infections and associated inflammation. Indeed, increasing epidemiological and preclinical studies have provided substantial support to the association between maternal immune activation (MIA) during gestation and an increased susceptibility in the offspring to develop various psychiatric and neurological disorders, including (but not limited to) autism spectrum disorder (ASD) [ 1 , 2 , 3 , 4 , 5 ]. Specifically, several studies explored the correlation between intrauterine infections and altered fetal brain development, resulting in long-term cognitive and behavioral impairments due to the fetal inflammatory response, regardless of the specific pathogen involved [ 6 ].…”
Section: Introductionmentioning
confidence: 99%